Mosquito transgenic technologies to reduce plasmodium transmission - Fuchs,S; Nolan,T; Crisanti,A (Methods in Molecular Biology, 2013)
The ability to introduce genetic constructs of choice into the genome of Anopheles mosquitoes provides a valuable tool to study the molecular interactions between the Plasmodium parasite and its insect host. In the long term, this technology could potentially offer new ways to control vector-borne diseases through the suppression of target mosquito populations or through the introgression of traits that preclude pathogen transmission. Here, we describe in detail protocols for the generation of transgenic Anopheles gambiae mosquitoes based on germ-line transformation using either modified transposable elements or the sitespecific PhiC31 recombinase .© Springer Science+Business Media, LLC 2013.